Effect of Pb and Cd Elicitors on Growth and Content of Vetiver Oil Adventitious Root In Vitro of Vetiver (Vetiveria zizanioides L. Nash) - Ivani, Trecy; Widoretno, Wahyu (Graduate School, Universitas Brawijaya, 2019)
This research aimed to evaluate the effect of Pb and Cd elicitors on root growth and essential oil content of vetiver oil on the root culture of vetiver (Vetiveria zizanioides L. Nash). Roots were induced by culturing of the shoot on MS media supplemented with 0.1 mg.L-1 kinetin and 7 mg.L-1 NAA. Elicitation was done by culturing roots on MS media with 0.1 mg.L-1 kinetin and 7 mg.L-1 NAA + 0.1 mM Pb or Cd. Roots then observed for fresh weight, dry weight, number, and root length, and vetiver oil contents were analyzed using GC-MS. The addition of Pb and Cd heavy metal elicitor affected the formation and the content of vetiver oil compounds of root culture. Pb elicitor increased the number of roots, while Cd elicitor increased root length. However, the addition of Pb and Cd elicitor on culture media decreased the fresh weight and root dry weight. Fifty eight vetiver oil compounds in adventitious roots of vetiver plants were identified. The main compounds of vetiver oil in roots culture were Khusimone (6.94%), Khusimol (6.05%), Khusimene (4.85%), α Vetivone (3.70%), β Vetivone (3, 53%), Vetiverol (3.22%), Prezizaene (2.35%), and Zizaene (1.91%). Elicitation with Pb and Cd increased the composition of the main compounds of vetiver oil. Cd elicitor increased the composition of the main compound vetiver oil higher than the Pb elicitor. Keywords: adventives root, elicitor, in vitro, Pb and Cd, vetiver oil